KEPEMILIKAN INSTITUSIONAL, KEPUTUSAN INVESTASI DAN FAKTOR LAINNYA DALAM MEMENGARUHI NILAI PERUSAHAAN NONKEUANGAN - Ricky Leonardo Chandra; Umar Issa Zubaidi (E-Jurnal Akuntansi TSM, 2023)
Abstract: Good firm value in the eyes of the public is certainly what every company wants. This study aims to examine and obtain empirical evidence regarding the influence of institutional ownership, profitability, liquidity, dividend policy, debt policy, firm size, and investment decisions on firm value. Investors look at the firm's value as an indicator to evaluate a company before investing their money. This study uses a purposive sampling method. There are 90 nonfinancial companies listed on Indonesia Stock Exchange and have met the research criteria from 2019 to 2021, so there are 270 sample data used in this study. The testing of independent variables on dependent variables uses a multiple regression model. The proxies used in this study are financial ratios to measure profitability, liquidity, dividend policy, debt policy, and investment decision. The natural logarithm is also used in this study to measure firm size variable. The results of this study indicate that profitability, debt policy, and investment decision have positive effects on firm value. Meanwhile, institutional ownership, liquidity, dividend policy, and firm size have no effect on firm value.